2021
DOI: 10.1177/23328584211041350
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Educational Access in the Time of COVID: Evidence From a Nationally Representative Panel of American Families

Abstract: We use data collected between April 2020 and March 2021 from the Understanding America Survey, a nationally representative internet panel of approximately 1,450 households with school-age children, to document the access of American households to K–12 education during the COVID-19 crisis. We also explore disparities by parent race/ethnicity, income, urbanicity, partisanship, and grade level (i.e., elementary school vs. middle/high school). Results shed light on the vectors of inequality that occurred throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 17 publications
0
28
1
Order By: Relevance
“…Studies of gifted education with nationally representative samples have documented null effects on academic achievement (Adelson et al, 2012;Redding & Grissom, 2021), although it is important to emphasize that in being nationally representative, the researchers could not tease out exactly what services, if any, the students received. In the United States, advanced learning does not appear to be a priority-even less in the COVID-19 era (Haderlein et al, 2021)-and on average (and this is important since there are excellent gifted programs), typical gifted-specific programs appear to be effective at little aside from separating students based on race, ethnicity, and socioeconomic status. Because of this lackluster state of affairs, I am comfortable trying something new.…”
mentioning
confidence: 99%
“…Studies of gifted education with nationally representative samples have documented null effects on academic achievement (Adelson et al, 2012;Redding & Grissom, 2021), although it is important to emphasize that in being nationally representative, the researchers could not tease out exactly what services, if any, the students received. In the United States, advanced learning does not appear to be a priority-even less in the COVID-19 era (Haderlein et al, 2021)-and on average (and this is important since there are excellent gifted programs), typical gifted-specific programs appear to be effective at little aside from separating students based on race, ethnicity, and socioeconomic status. Because of this lackluster state of affairs, I am comfortable trying something new.…”
mentioning
confidence: 99%
“…There was tremendous variation in how schools operated between and even within districts; affluent communities could rely on students’ and parents’ access to high‐speed internet, digital fluency, and personal devices to make lessons and materials available on various virtual platforms (Haderlein et al., 2021 ). In low‐income families, who in the U.S. are disproportionately Black and Latinx because of structural racism, parents were less likely to be able to work from home and had inequitable access to broadband internet and personal computing devices, limiting their ability to support and supervise homework assignments or help children log‐in to virtual class meetings (Haderlein et al., 2021 ; Oster, 2021 ). In‐person relationships, often so important to sustaining positive, reciprocal connections between home and school (Hong, 2019 ), shifted to the virtual space overnight.…”
Section: Immigrant Mothers’ Educational Aspirations and Advocacy For ...mentioning
confidence: 99%
“…Over the past year, researchers and educators alike have struggled to respond to the pandemic (DeMatthews et al, 2020), an ongoing crisis well beyond the experience or preparation of most schools and their leaders (DeMatthews et al, 2021; McLeod & Dulsky, 2021). This has resulted in a growing body of scholarship on COVID-19, most of which has documented (1) the impact on students, especially around academic achievement and mental health (Haderlein et al, 2021; Kuhfeld et al, 2020; Savitz-Romer et al, 2021); (2) crisis-leadership advice for educational leaders and policymakers (Chang-Bacon, 2021; Lowenhaupt & Hopkins, 2020; Netolicky, 2020; O’Connell & Clarke, 2020; Rigby et al, 2020; Starr, 2020); and (3) educators’ concerns about the pandemic (Hamilton et al, 2020). Reports also documented policy responses—such as how many days of school were cancelled on average, what kind of remote learning was offered, or how schools reopened (Hoffman et al, 2021; Malkus et al, 2020)—as well as what educators and policymakers did to combat the disparate conditions experienced by diverse students in underresourced or “vulnerable” schools (Organisation for Economic Co-operation and Development [OECD], 2020, p. 2).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In a nationally representative sample of principals from April-May 2020, a majority reported that, on reopening, they would place a higher priority on emergency preparation, addressing academic disparities, ensuring students' health/safety, and engaging with families (Hamilton et al, 2020). One study found the goal to enhance access to technology was met over time; differences across lines of race, income, and urban/rural contexts diminished from April-October 2020, but they did not fully disappear, especially for Black families (Haderlein et al, 2021).…”
Section: School Leader Concerns and Responses To Covid-19mentioning
confidence: 99%